Vegetative Indices in Assessing Effectiveness of the Photobioacoustic Complex in Children with the Vegetative Nervous System Somatoform Dysfunction, often Suffering from Acute Recurrent Infections - Natalya G. Kulikova; Tatyana V. Konchugova; Inna V. Volkova; Albina S. Tkachenko (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Photobioacoustic methods of complex exposure allow correcting vegetative, vascular-cardiac disorders in children with autonomicnervous system somatoform dysfunction syndrome (ANSSDS) without pharmacological load. Aim. To optimize the treatment of children with somatoform vegetative dysfunction (ANSSDS), often suffering from recurrent infections,using physiotherapy methods.The aim of the study was to optimize the treatment of children with somatoform vegetativedysfunction, often suffering from recurrentinfections, using physiotherapy methods. Material and methods. The study included 140 children with autonomic nervous system somatoform dysfunction syndrome (ANSSDS),often suffering from recurrent infection. For the first time, clinical complaints, functional (ECG and cardiointerval recording KIR)and vegetative indicators (Kerdo, Hildebrandt index, Biend, Baoev-Parin) before/after application of the innovative photobioacousticcomplex, including: BАС-BFB-bioacoustic effects on the head and LLLR on the projection of the cubital region and thymus were analyzed.The duration of the procedure was 30 minutes and the course of treatment was 10 procedures. Before and after the procedures,vegetative indices and indicators of myocardial bioelectrogenesis were examined, comparing them with the norm in healthy children. Results. 35% of children were diagnosed with parasympathicotonia (sympathetic imbalance -SI); 54.1% - sympathetic (SA) and10.9% - mixed (etonia - E) type of vegetative dystonia. There were reveled gender-age differences in subjective complaints of childrenwith ANSSDS, whose index vegetative indicators were correlated with the type of vegetative support. Children with SA were 2.5 timesmore likely to be diagnosed with cardiac syndrome and elevated blood pressure; in children with SI - 3.5 times more often detected:gastric, astheenoeurotic syndrome and allergic diseases; in children with E: asthenonevrotic, neurosis-like disorders and sleep disturbancesthat were differentiated after the use of photobioacoustic complex. Complaints and vegetative indices in children with SI andE were corrected more significantly than in SA. Conclusion. Evaluation of vegetative indicators in children 7-12 years with ANSSDS, often suffering from recurrent infection, allows topersonify treatment programs and reduce the level of acute recurrent morbidity by 2.5 times.